How Does Owners' Exposure to Idiosyncratic Risk Influence the Capital Structure of Private Companies? - Elisabeth Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper identifies the entrepreneur's exposure to idiosyncratic risk as an important determinant of the demand for loans and the capital structure. The analysis is based on a sample of small and medium-sized private companies from the United States. The exposure to idiosyncratic risk is approximated by the share of personal net worth invested in one company (SNWI). Exposure to idiosyncratic risk increases the cost of equity capital, since higher equity returns are required as compensation. This therefore makes bank financing more attractive. We find that SNWI increases both the demand for new bank loans and leverage substantially.
Older version: http://hdl.handle.net/10419/24107
Keywords: G32; G30; 330; capital structure; exposure to idiosyncratic risk; private companies; Kapitalstruktur; Eigenkapital; Kapitalkosten